(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Simulation imitates a real-life scenario to provide a life-like experience in a controlled environment. Simulation training teaches trainees the skills needed in the real world. This study assessed the effectiveness of hotel simulation learning as a tool for decision-making. Given the difficulties in educating students for the service sector, it allows them to base hypothetical choices on real-world events. The perceived learning experience may improve students’ capacity for using critical thought to control various operational tactics. The researcher used a descriptive research method to focus on the effectiveness of the BSHRM program from the perspective of Bestlink College Philippines students. The study focused on 50 BSHRM graduates of Bestlink College of the Philippines. The researchers found 50 graduated students from BSHRM as the respondents to accomplish the study. It was noted that the age group of 22-24 years old ranked at 48%, and according to gender, 48% were male, 54% were female, and 92% of the respondents were single, while the remaining 8% were married. Seventy-eight percent of the respondents were employed, and 11% were unemployed. Respondents/employees have used the simulation activities in their work, and it enhanced their skills. Based on the gathered data and conclusions, researchers proved that the simulation is effective, based on the result of finding that many graduated students are using what they learned in simulation and applying it to themselves. It helps to enhance their skills and is very helpful to their work.